A case study of women's job-seeking opportunities and work experiences in a hotel in Iloilo. - Roquios, Wendyflor
This study on "Women's Job-seeking Opportunities and Work Experiences in a Hotel in Iloilo City" examines the working conditions of women employees and the gender culture of Amigo Terrace Hotel. It provides an analysis of relevant issues related to gender and the workplace., Amigo Terrace Hotel is a subsidiary of the La Filipina Uygongco Corporation, owned by families belonging to the Uygongco clan of Iloilo City. At present it has one hundred forty-six (146) regular employees, sixty-four (64) women and eighty (82) men. There is a numerical dominance of men but it is usually the women who occupy supervisory positions. At present, among the six departments of the hotel, four supervisory positions are handled by women who have worked with the hotel for more than ten years. Aside from the supervisory positions, there are clerical jobs in some of the hotel's departments; but most other jobs are of a domestic nature, such as cleaning and cooking. The management has different qualifications for employees for each department depending on the kind of work there is. However, there does not appear to be a marked difference in the way women and men are hired and treated in their specific work environments. Men and women employees of the Amigo Terrace Hotel enjoy equal benefits and privileges according to their positions in the hotel hierarchy. Nevertheless, some degree of occupational segregation is felt by employees belonging to subordinate ranks and positions. Since most supervisory positions are occupied by women, they appear to have more privileges compared with men.